2018
DOI: 10.1007/s11259-018-9720-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of three-dimensional spheroid culture on equine mesenchymal stem cell plasticity

Abstract: Mesenchymal stem cells (MSCs) are useful candidates for tissue engineering and cell therapy fields. We optimize culture conditions of equine adipose tissue-derived MSCs (eAD-MSCs) for treatment of horse fractures. To investigate enhancing properties of three-dimensional (3D) culture system in eAD-MSCs, we performed various sized spheroid formation and determined changes in gene expression levels to obtain different sized spheroid for cell therapy. eAD-MSCs were successfully isolated from horse tailhead. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Macrophages may inhibit osteocyte viability through the effect of TNF-α and IL-6 in the model of monosodium urate crystal-induced inflammation [87]. During the stage of bone repair, expression of IL-18 from macrophages may serve an important role by increasing expression during bone formation or decreasing expression in the model of bisphosphonate-related osteonecrosis of the jaw [88,89]. Osteocytes may be regulated by macrophage secreting inflammatory cytokines (TNF-α, IL-6) to influence bone turnover.…”
Section: The Effect Of Macrophages In Osteocytesmentioning
confidence: 99%
“…Macrophages may inhibit osteocyte viability through the effect of TNF-α and IL-6 in the model of monosodium urate crystal-induced inflammation [87]. During the stage of bone repair, expression of IL-18 from macrophages may serve an important role by increasing expression during bone formation or decreasing expression in the model of bisphosphonate-related osteonecrosis of the jaw [88,89]. Osteocytes may be regulated by macrophage secreting inflammatory cytokines (TNF-α, IL-6) to influence bone turnover.…”
Section: The Effect Of Macrophages In Osteocytesmentioning
confidence: 99%
“…IL-6 was initially considered a proinflammatory cytokine, but this is a very simplistic view as this effect will depend on its concentration, distribution and synergy with other factors ( Kristiansen and Mandrup-Poulsen, 2005 ). Studies have shown that 3D cultured MSC have shown increased secretion of IL-6, and this would be an inducible factor of angiogenesis ( Parket al., 2018 ; Xie et al., 2017 ) and improve the antifibrotic potential ( Zhang et al., 2016 ). Specifically in relation to type 1 diabetes, studies demonstrated that this cytokine is not cytotoxic to beta cells and even shows a protective effect on beta cells lineage and mouse islets in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Equine mesenchymal stem cells (MSC), derived from bone marrow or fatty tissue, are mainly used for this purpose (Arnhold, Absenger, Klein, Addicks, & Schraermeyer, 2007; Arnhold, Elashry, Klymiuk, & Wenisch, 2019). MSC are ideal for tissue engineering and cell therapy for the musculoskeletal structures because they can differentiate into different mesenchymal cell lines like for example chondrocytes or osteocytes and are easy to obtain (Bara, McCarthy, Humphrey, Johnson, & Roberts, 2014; Park et al., 2018).…”
Section: Equine Endothelial Progenitor Cellsmentioning
confidence: 99%